2020
DOI: 10.1111/anec.12783
|View full text |Cite
|
Sign up to set email alerts
|

The de Winter ECG pattern: Distribution and morphology of ST depression

Abstract: Background The reported positive predictive value (PPV) for the “de Winter ECG pattern” to predict an acute left anterior descending artery (LAD) lesion is inconsistent. Besides, the morphology of upsloping or nonupsloping ST depression (STD) may have different significance of severity and prognostication. Methods We searched the MEDLINE database using “de Winter” or “junctional ST‐depression with tall symmetrical T‐waves” or “tall T wave” or “STEMI equivalent” as the item up to March 2020. We compared the ECG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 65 publications
0
13
0
Order By: Relevance
“…The location of the upsloping STD in the precordial leads seemed to be associated with the culprit artery. A systematic review of 70 cases of the de Winter ECG pattern reported that upsloping STD from V 2 to V 4 centered on V 3 had a high positive predictive value for LAD occlusion (Zhan, Li, Han, et al, 2020 ). Tsutsumi K (Tsutsumi & Tsukahara, 2018 ) reported a case of a de Winter pattern in leads II, III, aVF, and V 4 –V 6 associated with a predominantly large RCA culprit in an inferoposterior myocardial infarction.…”
Section: Discussionmentioning
confidence: 99%
“…The location of the upsloping STD in the precordial leads seemed to be associated with the culprit artery. A systematic review of 70 cases of the de Winter ECG pattern reported that upsloping STD from V 2 to V 4 centered on V 3 had a high positive predictive value for LAD occlusion (Zhan, Li, Han, et al, 2020 ). Tsutsumi K (Tsutsumi & Tsukahara, 2018 ) reported a case of a de Winter pattern in leads II, III, aVF, and V 4 –V 6 associated with a predominantly large RCA culprit in an inferoposterior myocardial infarction.…”
Section: Discussionmentioning
confidence: 99%
“…Initially, the de Winter ECG pattern was considered a stable condition until reperfusion (Winter et al., 2008). However, several studies have demonstrated that this ECG pattern may be a transient ECG phenomenon (Zhan et al., 2020). In our case, we observed a dynamic evolution from the de Winter ECG pattern to STEMI within four hours, which was associated with an occlusion proximal to the LAD artery, as (Wei‐Wei et al., 2019) reported.…”
Section: Discussionmentioning
confidence: 99%
“…10,13 The shape of the ST depression may denote the difference of severity and extent of myocardial ischemia, anatomical different, and myocardial protection with the upsloping pattern was the most severe form than non-upsloping (horizontal and downsloping) for the dWP. 14 Subendocardial ischemia in the early time results dWP to appear, when ischemia is progressed into transmural ischemia the STEMI pattern will appear with classic diastolic and systolic current of injury mechanism. It can be hypothesized that there was a time when the ischemia expanded from the subendocardium to the epicardium that showed the evolution of the STsegment.…”
Section: Discussionmentioning
confidence: 99%